Cannabinoid receptors in the inflammatory cells of canine atopic dermatitis - Chiocchetti, Roberto; Salamanca, Giulia; De Silva, Margherita; Gobbo, Francesca; Aspidi, Francesca; Cunha, Rodrigo Zamith; Galiazzo, Giorgia; Tagliavia, Claudio; Sarli, Giuseppe; Morini, Maria (Frontiers in Veterinary Science, 2022)
Background: Atopic dermatitis (AD) is one of the most common cutaneous inflammatory and pruritic diseases in dogs. Considering its multifactorial nature, AD can be a challenging disease to manage and the therapeutic strategy must often be multimodal. In recent years, research has been moving towards the use of natural products which have beneficial effects on inflammation and itching, and no side effects. Cannabinoid receptors have been demonstrated to be expressed in healthy and diseased skin; therefore, one of the potential alternative therapeutic targets on investigating AD is the endocannabinoid system (ECS). Objective: To immunohistochemically investigate the expression of the cannabinoid receptor type 2 (CB2R), and the cannabinoid-related receptors G protein-coupled receptor 55 (GPR55), transient receptor potential vanilloid 1 (TRPV1) and ankyrin 1 (TRPA1) in mast cells (MCs), macrophages, T cells, and neutrophils of the skin of dogs with AD. Animals: Samples of skin tissues were collected from eight dogs with AD (AD-dogs). Materials and Methods: The immunofluorescent stained cryosections of the skins of 8 dogs with AD having antibodies against CB2R, GPR55, TRPV1, TRPA1 were semiquantitatively evaluated. The inflammatory cells were identified using antibodies against tryptase (mast cells), ionized calcium binding adaptor molecule 1 (IBA1) (macrophages), CD3 (T cells), and calprotectin (neutrophils). The proportions of MCs, macrophages, T cells, and neutrophils expressing CB2R, GPR55, TRPV1 and TRPA1 were evaluated. Results: The cells of the inflammatory infiltrate showed immunoreactivity (IR) for all or for some of the cannabinoid and cannabinoid-related receptors studied. In particular, MCs and macrophages showed CB2R-, GPR55-, TRPA1-, and TRPV1-IR; T cells showed CB2R-, GPR55- and TRPA1-IR, and neutrophils expressed GPR55-IR. Co-localization studies indicated that CB2R-IR was co-expressed with TRPV1-, TRPA1-, and GPR55-IR in different cellular elements of the dermis of the AD-dogs. Conclusions and clinical importance: Cannabinoid receptor 2, and cannabinoid-related receptors GPR55, TRPV1 and TRPA1 were widely expressed in the inflammatory infiltrate of the AD-dogs. Based on the present findings, the ECS could be considered to be a potential therapeutic target for dogs with AD, and may mitigate itch and inflammation.